Pesticide use in Sub-Saharan Africa: Estimates, projections, and implications in the context of food system transformation - Snyder, Jason E; Smart, Jenny; Goeb, Joseph C.; Tschirley, David (Agricultural and Applied Economics Association, 2019)
The purpose of this paper is to characterize pesticide use in developing Sub-Saharan Africa (dSSA) in the context of urbanization, income growth, and food system change. To do this we (1) estimate some of the correlates of pesticide use worldwide and use them to predict trends in SubSaharan Africa through 2040, and (2) present new household survey results on pesticide purchase behavior by horticultural farmers supplying urban markets in Zambia and Mozambique. Our analysis shows that income per capita and population are positive and significant drivers of pesticide use, while surprisingly, urbanization, if controlling for other factors, is actually a negative driver, along with agricultural share of GDP. Our model predicts that total pesticide use in d-SSA will increase by a factor of 1.24 to 2.32 - depending on the income growth scenario - but will still be low compared to the rest of the world.